Detection of amines with extended distyrylbenzenes by strip assays - Kumpf, Jan; Freudenberg, Jan; Fletcher, Katharyn M.; Dreuw, Andreas; Bunz, Uwe H. F. (The journal of organic chemistry, 2014)
We herein describe the synthesis and property evaluation of three novel aldehyde-substituted pentameric phenylenevinylenes carrying branched oligo(ethylene glycol) (swallowtail, Sw) substituents. The targets were synthesized by a combination of Heck coupling and Wittig or Horner reactions of suitable precursor modules. If the pentameric phenylenevinylene carries only two of these Sw substituents, it is no longer water-soluble. When six of the Sw substituents are attached, regardless of their position, the pentameric phenylenevinylenes are well water-soluble. The dialdehydes were investigated with respect to their amine-sensing capabilities both in water as well as in the solid state, sprayed onto thin layer chromatography (TLC) plates (alox, silica gel, reversed phase silica gel). The recognition of amine vapors using the sprayed-on phenylenevinylene dialdehydes is superb and allows the identification of different amines on regular silica TLC plates via color changes, analyzed by a statistical tool, the multivariate analysis of variance (MANOVA) protocol.